Performance-Based Incentives and Workforce Productivity in Small Enterprises: Insentif Berbasis Kinerja dan Produktivitas Tenaga Kerja di Usaha Kecil - Yuanis, Yuanis (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Small-scale enterprises are vital to Indonesia’s economic fabric, yet they often face challenges in optimizing employee productivity due to limited resources and informal management practices. Specific Background: Incentive systems, particularly in micro and small enterprises (MSEs), are frequently underdeveloped, with little empirical analysis on their effectiveness. Knowledge Gap: Existing literature lacks integrated insights on how both financial and non-financial incentives, coupled with job satisfaction, influence productivity within MSE contexts. Aims: This study investigates the extent to which performance-based incentives affect employee productivity at UD. Budi Karya Jarorejo, a representative MSE in Tuban Regency. Results: Employing a mixed-methods approach, the research finds that financial incentives significantly enhance productivity, while non-financial incentives contribute positively, particularly for intrinsically motivated employees. In contrast, job satisfaction alone does not yield substantial productivity gains without proper incentive mechanisms. Novelty: The study provides context-specific evidence on the interplay between incentive types and employee motivation in MSEs, an area previously underexplored. Implications: These findings underscore the need for fair and transparent incentive structures to build a sustainable and performance-oriented work culture in small enterprises, offering practical guidance for policy and management innovation in Indonesia’s MSE sector. Highlights: Financial incentives have the strongest impact on boosting employee productivity. Non-financial incentives matter, especially for intrinsically motivated employees. Job satisfaction alone isn't enough to drive productivity without clear incentive systems. Keywords: Performance-Based Incentives, Financial Incentives, Non-Financial Incentives, Employee Productivity, Small Enterprises